Discovery of distal ejecta from the 1850 Ma Sudbury Impact Event - Addison, W.; Brumpton, G.; Vallini, D.; Davis, D.; Kissin, S.; Fralick, P.; McNaughton, Neal; Hammond, A. (Geological Society of America Inc, 2005)
A 25?70-cm-thick, laterally correlative layer near the contact between the Paleoproterozoic sedimentary Gunflint Iron Formation and overlying Rove Formation and between the Biwabik Iron Formation and overlying Virginia Formation, western Lake Superior region, contains shocked quartz and feldspar grains found within accretionary lapilli, accreted grain clusters, and spherule masses, demonstrating that the layer contains hypervelocity impact ejecta. Zircon geochronologic data from tuffaceous horizons bracketing the layer reveal that it formed between ca. 1878 Ma and 1836 Ma. The Sudbury impact event, which occurred 650?875 km to the east at 1850 1 Ma, is therefore the likely ejecta source, making these the oldest ejecta linked to a specific impact. Shock features, particularly planar deformation features, are remarkably well preserved in localized zones within the ejecta, whereas in other zones, mineral replacement, primarily carbonate, has significantly altered or destroyed ejecta features.